MARKET REACTIONS TOWARDS THE ANNOUNCEMENT OF SUKUK ISSUANCE: EVIDENCE FROM GULF MARKETS - EL MAJDOUB, Nabil (African Scientific Journal, 2021)
Sukuk (Islamic bonds) emerged as a revolutionary financial instrument over the last years and is considered as the flagship capital market instrument of the Islamic finance industry. However, the understanding of it is still limited compared to conventional bonds. This study aims to investigate whether the announcements of Sukuk issuance that carry any new information can create impact on the market’s reactions using 42 Sukuk announcements over the period of 2010 to 2019 in four Gulf financial markets. It is revealed the absenteeism of significant abnormal returns across asymmetric and symmetric event windows for periods before and after the announcement date, concluding no wealth effect. Within the equity marketplace, these results will be of practical relevance to corporations, practitioners and decision-makers.